Perlindungan Hukum Terhadap Pemilik Hak Terkait Atas Hak Cipta Yang Karya Lagunya Digunakan Tanpa Izin Pada Aplikasi Tiktok (Studi Kasus PT Digital Rantai Maya dan Tiktok PTE., Ltd) - Ghinartieka, Vidya Auranti (UNES Law Review, 2024)
Law Number 28 of 2014 concerning Copyright not only protects the rights of creators or their creations, but also protects the rights of people who display or distribute a work to the public, which are called Related Rights. Phonogram producers as holders of related rights have economic rights to their sound recordings, but it is not impossible that there will be violations of related rights to copyright, as happened between PT Digital Chain Maya and TikTok Pte., Ltd. This research will discuss how legal protection is for owners of related rights for copyright whose song works are used without permission on the Tiktok application and what forms of accountability can be carried out by TikTok to owners of related rights for copyright whose song works are used without permission on the Tiktok application. . This research uses descriptive normative legal research methods. Based on the research results, it is concluded that the Copyright Law has provided legal protection for Related Rights owners whose song works are used without permission in the TikTok application, as stated in Article 24 paragraph (4) and also legal protection from the agreement between the Related Rights owners and TikTok. The form of responsibility from TikTok to the owners of Related Rights whose song works are used without permission on its services is in the form of economic responsibility, namely by providing appropriate compensation.